Cane Hay Cost-Return Budget (W-CH-F Rotation) in Western Kansas - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1996)
This publication estimates the costs and returns associated with a typical sorghum sudangrass hybrid planted at heavier seeding rates and harvested as a hay crop in western Kansas.
MF997_1996_10
Keywords: MF997; Economics; Crops; MF